Cladóceros fitófilos (Crustacea, Branchiopoda) respondem a um gradiente latitudinal de diversidade em planícies de inundação tropicais?. - Rocha, Mariana Perez (2014)
The determining factor of biological diversity is not exactly latitude itself, but the variables more correlated to latitude acting as proxy for biodiversity on Earth. The assessment of biodiversity and richness distribution of cladocerans ranged the phytophilic fauna of four Brazilian floodplain ecossystems, Amazon, Araguaia River, Southern Pantanal Mato-grossense, and Paraná River, integrated in a latitudinal gradients scale as well as the major environmental factors to establish such distribution. The hypothesis tested was: that there is a greater cladocerans richness associated with aquatic macrophytes in the Amazon and Araguaia plains for a greater diversity of such organisms can be found in lower latitudes. Additionally, it was ascertained the difference in the abundance of these microcrustaceans among the floodplains. The group of cladocerans associated with aquatic macrophytes was verified as represented by 45 species distributed in seven families, being Chydoridae the most specious (27 species). Through Permanova, the data analyzed presented no latitudinal gradient in the diversity of phytophylic cladocerans in Brazilian floodplains for Pantanal proved more diverse in species than the Araguaia plains, characterizing thus no true latitudinal gradient of species for the four plains. The limnological factors presented effects on the composition and abundance of species in the four plains analyzed for a separation and similar composition for the fours systems became clear through RDA analysis.